2012
DOI: 10.1038/nm.2666
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling nanocomplexes by combining ferumoxytol, heparin and protamine for cell tracking by magnetic resonance imaging

Abstract: We report on a novel and straightforward magnetic cell labeling approach that combines three FDA-approved drugs, ferumoxytol (F), heparin (H) and protamine (P) in serum free media to form self-assembling nanocomplexes that effectively label cells for in vivo MRI. We observed that the HPF nanocomplexes were stable in serum free cell culture media. HPF nanocomplexes exhibited a three-fold increase in T2 relaxivity compared to F. Electron Microscopy revealed internalized HPF within endosomes, confirmed by Prussia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
212
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(238 citation statements)
references
References 36 publications
26
212
0
Order By: Relevance
“…The PFC-based cell labeling agent was designed and optimized specifically for clinical MRI. Prior clinical MRI cell tracking work (e.g., de Vries et al) (14) has relied on off-label use of metal-ion-based nanoparticles, often in conjunction with transfection agents (15). Historically, various PFC molecules have been contemplated for clinical use as artificial oxygen carriers (16) in large doses ($10 g/kg).…”
Section: Resultsmentioning
confidence: 99%
“…The PFC-based cell labeling agent was designed and optimized specifically for clinical MRI. Prior clinical MRI cell tracking work (e.g., de Vries et al) (14) has relied on off-label use of metal-ion-based nanoparticles, often in conjunction with transfection agents (15). Historically, various PFC molecules have been contemplated for clinical use as artificial oxygen carriers (16) in large doses ($10 g/kg).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies, however, have shown that iron oxide labeling, combined with magnetic targeting, might improve graft retention in the rat heart [29,30,34,36]. Thus, ferumoxytol cell labeling might have utility in both in vivo cardiac graft imaging and cell retention.…”
Section: Mri Of Labeled Hesc-cpcs In the Pig Heart ©Alphamed Press 2016mentioning
confidence: 99%
“…Ferumoxytol interacts with cells via a synthetic carbohydrate coating and is currently used for the treatment of iron-deficiency anemia in the presence of chronic kidney disease [32]. Furthermore, ferumoxytol displays limited cytotoxicity and genotoxicity and might improve the viability of certain cell populations (i.e., microglia) [14,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Transplanted stem cells can be assessed for long-term periods using noninvasive imaging techniques [66,67]. Stem cells can be tracked in vivo after their transplantation using different strategies: initial labeling of stem cells with fluorescent dyes or magnetic nanoparticles, such as superparamagnetic iron oxide, and stem cell transfection with several reporter genes such as the LacZ and green fluorescence protein (GFP) [68,69]. The visualization of the labeled stem cells requires either simple, or complex and sophisticated imaging systems such as MRI [66,70,71], computed tomography imaging [72], PET and single-photon emission computed tomography imaging [73].…”
Section: Nanomedicine: a Giant Leap Forward In Disease Diagnosis And Trmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles (60-150 nm in diameter) are composed of biodegradable and recyclable iron and are coated with dextran or carboxydextran to prevent aggregation and ensure aqueous solubility [74,75]. Magnetic nanoparticles can attach to the stem cell surface, but are also capable of being internalized by phagocytosis or, more often, by endocytosis [76], a process that is often facilitated by the use of coating and membrane receptor-binding agents [69,77]. Endocytosis of magnetic nanoparticles does not affect stem cell viability, growth, fate or differentiation [78].…”
Section: Nanomedicine: a Giant Leap Forward In Disease Diagnosis And Trmentioning
confidence: 99%